Development planning for the Oyu Tolgoi panel cave mine - Crook, K.; Prince, F. (Caving 2018: Proceedings of the Fourth International Symposium on Block and Sublevel Caving, 2018)
Oyu Tolgoi is a large panel cave mine currently under construction in the Gobi Desert of Mongolia. Due to the overall length of the Hugo North orebodyat Oyu Tolgoi stretching almost 2 km, the Lift 1 production area has been split into three production panels. These panels in turn have been sub-blocked into smaller, more manageable segments for development. Panel 0 (P0) was broken into P0A and P0B, southern and northern halves respectively, for the sequencing of development activities. The overall sequence philosophy for the panel is to fully develop these sub-panels and hand them over for production activities. The isolation of activities is seen as a risk reduction because it reduces the interactions between the undercutting and development activities. This paper will discuss the strategies followed for development of such a large-scale underground production panel, including the development sequence, undercut initiation, and the challenges of executing a project in a remote area of the world.